On the Green’s formula for a Stokes type problem - Skujus, Mindaugas (Lietuvos matematikos rinkinys, 2008)
A time-periodic Stokes problem is studied in the domain with cylindrical outlets to infinity. Using the Fourier series the problem is reduced to a sequence of elliptic problem. For each of these elliptic boundary value problems a generalized Green’s formula is constructed. The analogous Green’s formula for the steady Stokes problem was obtained in [1].
Keywords: cylindrical outlets to infinity; time-periodic Stokes problem; generalized Green’s formula